EFFICIENCY-BASED RATIONALES FOR NOTICE OF DEFAULT AND ANTICIPATED MATURITY IN ROMANIAN CIVIL LAW - Ungureanu, Iulia Georgiana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
This study examines the efficiency-based rationales underlying notice of default and anticipated maturity in Romanian civil law, with particular focus on Articles 1417, 1418, 1522, and 1523 of the Civil Code. The analysis highlights the dual function of the debtor’s default: preserving contractual equilibrium through a rebuttable presumption of tolerance, while safeguarding creditor interests by enabling access to remedies. Notice of default operates as an economically efficient mechanism, balancing favor contractus with the creditor’s right to damages, while default by operation of law accelerates access to remedies through absolute presumptions that exclude tolerance of delay. A central inquiry concerns the interplay between forfeiture of the benefit of term and the debtor’s default: whether anticipated maturity may be triggered by default situations, and conversely, whether forfeiture may automatically imply default.